Educating and training a workforce for nutrition in a post-2015 world - Fanzo, Jessica; Graziose, Matthew M.; Kraemer, Klaus; Gillespie, Stuart; Johnston, Jessica L.; de Pee, Saskia; Monterrosa, Eva; Badham, Jane; Bloem, Martin W.; Dangour, Alan D.; Deckelbaum, Richard; Dobermann, Achim; et al. (Elsevier, 2015)
Nearly all countries in the world today are burdened with malnutrition, manifesting as undernutrition, micronutrient deficiencies, and/or overweight and obesity. Despite some progress, efforts to alleviate malnutrition are hampered by a shortage in number, skills, and geographic coverage, of a workforce for nutrition. Here, we report the findings of the Castel Gandolfo workshop, a convening of experts from diverse fields in March 2014 to consider how to develop the capacity of a global cadre of nutrition professionals for the post-2015 development era. Workshop participants identified several requirements for developing a workforce for nutrition, including an ability to work as part of a multisectoral team; communication, advocacy, and leadership skills to engage decision makers; and a set of technical skills to address future challenges for nutrition. Other opportunities were highlighted that could immediately contribute to capacity development, including the creation of a consortium to link global North and South universities, online training modules for middle managers, and practical, hands-on experiences for frontline nutrition workers. Institutional and organizational support is needed to enable workshop recommendations on education and training to be effectively implemented and sustained. The findings from the Castel Gandolfo workshop can contribute to the delivery of successful nutrition-relevant actions in the face of mounting external pressures and informing and attaining the forthcoming Sustainable Development Goals.